Distribuição da comunidade de epífitos vasculares em diferentes sítios na Floresta Nacional de Ipanema, Iperó, SP, Brasil - Bataghin, Fernando Antonio (2009)
Despite the importance of vascular epiphytes to depict the degree of local preservation, there is little research on this subject. The present research was performed in the National Forest of Ipanema (UTM 7.422.000 and 7.390.000 S; 216.000 and 248.000 W in the zone 23 south), located in the Munnicipality of Iperó, State of São Paulo, Brasil, and aimed to characterize the vascular epiphytic community, analyzing their vertical distribution and the correlation between different sites. Three sites were considered, the first in an open area, the second at the forest border and the third inside the forest. From each one 90 assorted trees with DBH ≥ 20 cm were sampled. The surveyed trees were divided into three tree strata: low trunk, high trunk, and canopy. Frequency and diversity parameters based on the occurrence of epiphytes in the strata and in the assorted trees were estimated. In the survey 21 species of 14 genera in five families were found. Two Bromeliaceae, Tillandsia recurvata and T. tricholepis, presented the highest importance values. The Shannon index of diversity was 2.272 (nats) for the whole epiphytic community. Holoepiphytes were the dominant type. High trunk was the most diverse stratum, followed by canopy and low trunk. The statistical analysis showed significant difference between the sites of open area and forest border, and between the sites of open area and inner forest, but there was no significant difference between the sites of forest border and inner forest. In the analysis of assorted trees, 38 tree species belonging to 37 genera and 20 families were identified; the index of Shannon for assorted trees was 2.835 (nats). The species that hosted the highest number of epiphytic species (11 species) and presented the largest absolute value (AV = 882) was Tipuana tipu (Fabaceae). The statistical analysis showed no significant difference between assorted tree species in the various sites and also showed no relationship between epiphytic species and assorted tree species. The data of this study highlight the importance of these abiotic factors in limiting the development of epiphytes, and specially the importance of disturbances of human origin in the differences in composition and distribution of the vascular epiphytic between sites.